Penerapan Konsep Good Corporate Governance Dalam Meningkatkan Nilai Perusahaan - Yusi Irensi Seppa (Indonesian Journal of Taxation and Accounting, 2024)
Increasing company value through increasing owner or shareholder income is the company's main goal. One aspect used in measuring company value is the implementation of a good corporate governance system. This research aims to find out how the concept of Good Corporate Governance is applied in increasing company value. The research method is qualitative with literature study or Library Research. The aim is to analyze the comparison of existing theories with previous theories in the research literature. Based on the research results, it can be concluded that company size has a positive and significant effect on company value in a positive direction indicating that if company size increases, company value will also increase. Dividend Payout Ratio (DPR) has a positive and insignificant effect on company value because the profits obtained are greater. divided into the research period is too small because large remaining profits are retained and used to increase internal funding sources thereby increasing total assets and reducing debt to total assets, Institutional Ownership has a positive and insignificant effect on company value, and independent commissioners have a significant positive effect on company value . It is necessary to analyze further regarding other GCG factors in applying the concept, especially in increasing company value so that this can provide information to companies and other researchers to be used as a reference in subsequent developments.